Sedimentation and Diffusion in Nanofluids in Rotating Systems of Metal Friction Elements of Brake (Part III) - Janahmadov, A.Kh.; Volchenko, N.А.; Javadov, M.Y.; Volchenko, D.A.; Fidrovskaya, N.N.; Zhuravlev, D.Yu.; Аleynikova, O.М.; Skrypnyk, V.S.; Slepuzhnikov, Ye.D. (Herald of Azerbaijan Engineering Academy, 2023)
To assess sedimentation, the gradient theory is applied to pressure, velocity, partial and specific volume, mass, and molar concentration, as well as the determination of the sedimentation coefficient. The diffusion of nanoparticles is characterized by the coefficient and its mobility in the liquid. Selection by molecular weight of various materials of nanoparticles is made. The results of experimental studies on a model band-shoe brake are presented, and the cooling efficiency is established.